„Command of Fathers”. A Discourse of Sorrow and Enthusiasm in the Struggle of Aromanians for Their Language and Ethnicity in Multicultural Balkan Societies - Nowicka, Ewa (Poznańskie Studia Slawistyczne, 2015)
Since 1962, when Zbigniew Gołąb has published his fundamental study on Aromanian language in Macedonia, in Polish literature, beyond his study, there was a little interest in Aromanians as an ethnic group and in their language. In this article, the author focuses on 1) the changes the Aromanian language has been undergoing in the recent times, 2) how the transformation of the social situation of Aromanians influences the development of the language. In the present days, the social function of the ethnic language is transformed from the language of everyday use to the language as a symbol, label, marker of ethnicity, used in the special occasions. Opinions expressed by Aromanian intellectuals about their ethnic language, role in Aromanian social life, and their dilemmas, sorrows and enthusiasm, as well as activities around the ethnic language are the main objects of interest in the paper. The empirical material, applied to this study, was collected during the anthropological field research the author conducted in the summer seasons from 2007 till 2010 in all countries of residence of Aromanians: Greece, Macedonia, Albania, Bulgaria, Serbia, Romania. The empirical material includes more than 50 recorded and transcribed interviews with the leaders of Aromanian ethnic movement, informal conversations and observation notes taken during Aromanian public events.